Behavioral Processes and Their Functional Realization in English and Vietnamese - Nguyen Thi Tu Trinh; Phan Van Hoa (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
This article discusses the four different experience realms of Behavioral Processes and the configuration patterns of English and Vietnamese Behavioral clauses on the account of lexicogrammatical structures and ideational meanings. Then the study presents the similarities and differences in experience realms of Behavioral Processes and the configuration patterns of Behavioral clauses between the two languages. Qualitative and contrastive methods were adopted in this study to analyze 657 English and 602 Vietnamese Behavioral clauses from fourteen English and twenty three Vietnamese short stories and novels in order to demonstrate the features of behavioral realms and their functional realization. Attention has been paid to interpreting a wide range of lexicogrammatical choices as well as various strands of functions realizing behavioral realms. The study reveals four realms of behavior namely Semiotic, Social, Biological and Physical. It also presents seven associated configuration patterns in English and Vietnamese. The study reveals that the distinctive nature of the two languages (English-as a synthetic language and Vietnamese-as an analytic language) brings about some differences in the realization of English and Vietnamese Behavioral clauses. Received 1th August 2020; Revised 2nd June 2021; Accepted 20th August 2021